2001
DOI: 10.4049/jimmunol.166.6.4216
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Deficient IL-2 Production in T Cells from Patients with Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a multifactorial autoimmune disease characterized by diverse cellular and biochemical aberrations, including decreased production of IL-2. Here we show that nuclear extracts from unstimulated SLE T cells, unlike extracts from normal T cells, express increased amounts of phosphorylated cAMP-responsive element modulator (p-CREM) that binds the −180 site of the IL-2 promoter. Nuclear extracts from stimulated normal T cells display increased binding of phosphorylated cAMP-resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
185
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 183 publications
(195 citation statements)
references
References 29 publications
8
185
0
1
Order By: Relevance
“…We first transfected primary human T and Jurkat cells, using a cell electroporation technique (11)(12)(13)(14), either with the plasmid-encoding cDNA (pcDNA)/Elf-1 plasmid, which encodes the full-length Elf-1 cDNA, or with the empty plasmid to establish the protein products of the Elf-1 gene. The cytoplasmic extracts from primary ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We first transfected primary human T and Jurkat cells, using a cell electroporation technique (11)(12)(13)(14), either with the plasmid-encoding cDNA (pcDNA)/Elf-1 plasmid, which encodes the full-length Elf-1 cDNA, or with the empty plasmid to establish the protein products of the Elf-1 gene. The cytoplasmic extracts from primary ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The isolation and purification of primary T lymphocytes and culture of Jurkat cells have been recently described (11,12).…”
Section: Lymphocyte Isolation and Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Interleukin-2 (IL-2) production in SLE T cells is decreased because of limited transcriptional activity of the IL-2 promoter due to increased expression of the repressor cAMP response element modulator (CREM) (9) and decreased expression of the p65 chain of nuclear factor B (NF-B), which leads to decreased NF-B activity (10). Our group recently demonstrated that substitution of the defective p65 subunit of NF-B enhanced TCR/CD3-mediated IL-2 production in SLE T cells (11).…”
mentioning
confidence: 99%
“…56 More recently, increased binding of a transcriptional inhibitor of IL-2 gene promoter, phosphorylated cAMP response element modifier (pCREM), in lupus T cells has been shown to underpin reduced IL-2 production. 57 Further, a defect involving Cbl, an adaptor protein that negatively regulates transmembrane signalling, has been shown. This abnormality has been suggested to underpin persistent hyperexpression of CD40 ligand (CD40L)L and resistance to tolerance induction.…”
Section: T-lymphocyte and Natural Killer (Nk) Cellmentioning
confidence: 99%